Enhancing Educational Quality Through the P4 Budgeting Model Based on BAA: A SWOT Perspective - Sonny Muhammad Ikhsan Mangkuwinata; Marwan; Munawar; Saiful Bahri; Najmudin; Jamaluddin (Jurnal Penelitian Pendidikan IPA, 2026)
Financial management plays a crucial role in improving educational quality; however, many educational foundations still struggle to integrate budgeting, accounting, and auditing into a comprehensive financial management framework. Previous studies have generally examined these functions separately, creating a research gap regarding the effectiveness of an integrated model in supporting educational quality and institutional sustainability. This study aims to analyze the implementation of the integrated P4–Budgeting, Accounting, and Auditing (P4-BAA) model at the Almuslim Peusangan Foundation and evaluate its contribution to educational quality improvement. This study employed a qualitative case study approach. Data were collected through semi-structured interviews with 15 purposively selected informants, including foundation leaders, financial managers, school principals, and administrative staff. Additional data were obtained through document analysis and direct observation. Data were analyzed using thematic analysis supported by NVivo software through coding, categorization, theme development, and triangulation. The findings show that the P4-BAA model strengthened financial planning, accountability, and transparency across educational units. Key strengths identified include institutional reputation, affordable tuition fees, and government support, while major challenges involve limited infrastructure, inadequate teacher qualifications, and unstable funding sources. The model improved budget allocation, stakeholder participation, financial reporting, and monitoring mechanisms, leading to more efficient resource utilization and stronger support for teacher development programs. The study concludes that the P4-BAA model provides a practical framework for enhancing financial governance and sustaining continuous improvements in educational quality.